Chaplaincy Visitation and Spiritual Care after Intracerebral Hemorrhage. Issue 4 (2nd October 2017) - Howell, Melissa L.; Schwab, Kristin; Ayres, Alison M.; Shapley, Dean; Anderson, Christopher D.; Gurol, M. Edip; Viswanathan, Anand; Greenberg, Steven M.; Rosand, Jonathan; Goldstein, Joshua N.
Abstract : To better understand factors influencing spiritual care during critical illness, we examined the use of spiritual care in patients hospitalized with intracerebral hemorrhage (ICH), a frequently disabling and fatal disease. Specifically, the study was designed to examine which demographic and clinical characteristics were associated with chaplain visits to critically ill patients. The charts of consecutive adults (>18) with spontaneous ICH presenting to a single academic medical center between January 2014 and September 2015 were reviewed. Chaplains visited 86 (32%) of the 266 patients. Family requests initiated the majority of visits (57%). Visits were disproportionately to Catholic patients and those with more severe injury. Even among Catholics, 28% of those who died had no chaplaincy visit. Standardized chaplaincy screening methods and note templates may help maximize access to spiritual care and delineate the religious and spiritual preferences of patients and families.